FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PERSALINAN RUPTUR PERINEUM DI RSIA SITTI KHADIJAH I MAKASSAR - Muhammad Fakhruddin (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
Objective: The purpose of this study was to see the factors related to the incidence of rupture perineum delivery. Method: In this study using the research design used in this study is cross sectional that researchers do observation or measurement of variables at one time. The amount of sample in this study 40 respondents who match the inclusion criteria. The data were collected using questionnaire. Results: The results showed that there was a relationship between parity and rupture perineum (p = 0,009), there was a correlation between birth spacing with perineum rupture (p = 0,004), there was correlation between infant weight with rupture perineum ( p = 0.002), and there was a correlation between birth history with rupture perineum (p = 0,007). Discussion: Deaths in pregnant and maternity women are a big problem in developing countries. Deaths that occur in fertile women in developing countries are around 25-50%. Maternal mortality is a benchmark for assessing the state of obstetric care in a country. Conclusion The conclusion in this study is that there is a relationship between parity, birth spacing, infant weight and birth history with rupture perineum. Suggestion: Suggestions from the results of this study can be used as motivation and input for mothers who do labor in order to work together and comparative when performing a smooth running process and not having rupture of the perineum